2006
DOI: 10.1007/s00442-005-0344-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of an insect–plant interaction following habitat loss and experimental wetland restoration

Abstract: This study examined the impact of wetland habitat loss and isolation on an insect-plant interaction, and the subsequent rate of recovery of the interaction following experimental habitat restoration. We compared herbivore colonisation rates and herbivory damage by 'Batrachedra' sp. (Lepidoptera: Coleophoridae) on experimentally placed potted Sporadanthus ferrugineus (Restionaceae) plants at increasing distances (up to 800 m) from an intact habitat (the source population). These tests showed that even a moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
0
15
0
3
Order By: Relevance
“…Numerous studies have shown the disruption of insect community trophic structure due to habitat loss and isolation (see review in Tscharntke et al ; Watts & Didham ). A few studies have shown that these can recover with restoration (Watts & Didham ; Gregoire Taillefer & Wheeler ). However, a meta‐analysis of wetland restoration sites found that biological structure and biogeochemical functioning remained approximately 25% lower than reference sites, even after a century of restoration (Moreno‐Mateos et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the disruption of insect community trophic structure due to habitat loss and isolation (see review in Tscharntke et al ; Watts & Didham ). A few studies have shown that these can recover with restoration (Watts & Didham ; Gregoire Taillefer & Wheeler ). However, a meta‐analysis of wetland restoration sites found that biological structure and biogeochemical functioning remained approximately 25% lower than reference sites, even after a century of restoration (Moreno‐Mateos et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Among control plots, there were essentially no differences between patch sizes in terms of arthropod density. Insect assemblages can be sensitive to isolation from source populations [60]. The similar assemblages in both restored habitat types suggests that mounds and terraces were equally isolated from the reference area, which was presumably the source of new arthropod recruits to the entire restored area.…”
Section: Discussionmentioning
confidence: 94%
“…A restauração funcional de um ecossistema requer o retorno dos links essenciais relacionados à estrutura das redes ecológicas Neste estudo, eles detectaram um aumento significativo em riqueza e do número de grupos funcionais que compõem as redes, assim como incremento na diversidade de interações das redes nas áreas restauradas. Em outros dois estudos, pesquisadores mostraram que a taxa de re-colonização de comunidades de invertebrados é bem rápida em áreas experimentais restauradas cujo foco foi a recomposição da comunidade vegetal (Watts & Didham 2006, Watts et al 2008. Os mesmo autores verificaram o retorno de uma espécie herbívora de borboleta e dos danos causados em uma espécie nativa das áreas úmidas na Nova Zelândia, avaliando o rápido retorno da interação planta-herbívoro (Watts & Didham 2006 …”
Section: Adams 1994)unclassified
“…Em outros dois estudos, pesquisadores mostraram que a taxa de re-colonização de comunidades de invertebrados é bem rápida em áreas experimentais restauradas cujo foco foi a recomposição da comunidade vegetal (Watts & Didham 2006, Watts et al 2008. Os mesmo autores verificaram o retorno de uma espécie herbívora de borboleta e dos danos causados em uma espécie nativa das áreas úmidas na Nova Zelândia, avaliando o rápido retorno da interação planta-herbívoro (Watts & Didham 2006 …”
Section: Adams 1994)unclassified
See 1 more Smart Citation